Application of Endoxylanases of Bacillus halodurans for Producing Xylooligosaccharides from Empty Fruit Bunch - Chanakan Thirametoakkhara; Yi-Cheng Hong; Nuttapol Lerkkasemsan; Jian-Mao Shih; Chien-Yen Chen; Wen-Chien Lee (My University, 2022)
Endo-1,4-β-xylanase catalyzes the random hydrolysis of β-1,4-D-xylosidic bonds in xylan, resulting in the formation of oligomers of xylose. This study aims to demonstrate the promise of endoxylanases from alkaliphilic Bacillus halodurans for the production of xylooligosaccharides (XOS) from oil palm empty fruit bunch (EFB) at high pH. Two enzyme preparations were employed: recombinant endoxylanase Xyn45 (GH10 xylanase) and nonrecombinant endoxylanases, a mixture of two extracellular endo-1,4-β-xylanases Xyn45 and Xyn23 (GH11 xylanase) produced by B. halodurans. EFB was first treated with an alkaline solution. Then, the dissolved xylan-containing fraction was retained, and a prepared enzyme was added to react at pH 8 to convert xylan into XOS. Compared with the use of only Xyn45, the combined use of Xyn45 and Xyn23 resulted in a higher yield of XOS, suggesting the synergistic effect of the two endoxylanases. The yield of XOS obtained from EFB was as high as 46.77% ± 1.64% (w/w), with the xylobiose-to-xylotriose ratio being 6:5. However, when the enzyme activity dose was low, the product contained more xylotriose than xylobiose. Four probiotic lactobacilli and bifidobacteria grew well on a medium containing XOS from EFB. The presence of XOS increased cell mass and reduced pH, suggesting that XOS promoted the growth of probiotics.
Keywords: Xylobiose; Biofuel production and bioconversion